PUBLIC BUREAUCRACY COLLABORATION: BARRIERS AND CHALLENGES THE ACADEMIC PERSPECTIVE - Shirazi, Ali (PEOPLE: International Journal of Social Sciences, 2017)
The decentralization, privatization and globalization have created a world without boarders and highly competitive markets, forcing firms to constantly innovate in order to survive, improve performance and grow. One approach for firms to innovate is to collaborate with universities. University-Industry Collaboration (U-IC) has proved to be very effective in developed world, but in most cases quite ineffective in developing countries. While many research have identified success or failure factors in collaborative efforts in developed world, not much known about it in developing world, and even less in their public bureaucracies. The purpose of this paper is to briefly review the existing literature on U-IC, focus on the reality of politics in public bureaucracies, namely university and municipality in developing countries, and identify prerequisites needed to be addressed before contemplating on any joint effort.